Fear of Missing Out (FoMO) dan Phubbing Behavior Pada Remaja Pengguna Tiktok di Jakarta Timur - Zein, Annisa Elya; Abdillah, Rijal (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of technology and social media, particularly TikTok, has influenced the way teenagers interact socially. One of the psychological phenomena that emerges is Fear Of Missing Out (FoMO), which is a feeling of anxiety for fear of being left out of ongoing social or digital activities. This condition encourages individuals to stay connected online and ignore in-person interactions, resulting in phubbing behavior. Phubbing is the act of ignoring others in social situations because it is too focused on the smartphone. This study aims to determine the effect of FoMO on Phubbing Behavior in adolescent TikTok users in East Jakarta. This study uses a quantitative method with a simple linear regression approach and involves 150 teen TikTok users selected through the Quota Sampling technique. The results showed that FoMO had a significant effect on phubbing behavior. Adolescents with high levels of FoMO tend to do phubbing more often. These findings emphasize the importance of awareness of the psychological impact of social media use on the quality of adolescent social interactions.